106k views
0 votes
If f(x)=4^x-8 and g(x)=5x+6 find (f+g)(x) ANSWER ASAP PLS

User Feng Smith
by
5.5k points

2 Answers

5 votes

Answer: 4^x+5x-2

Add up the equations and combine any like terms. In this case, the like terms are -8 and +6 which combine to -2. Everything else is unlike terms so you leave them as is.

f(x) + g(x) = (4^x-8) + (5x+6)

f(x) + g(x) = 4^x + 5x + (-8+6)

f(x) + g(x) = 4^x + 5x - 2

User Krolth
by
6.2k points
7 votes

Answer:


\large\boxed{(f+g)(x)=4^x+5x-2}

Explanation:


(f+g)(x)=f(x)+g(x)\\\\\text{We have:}\\\\f(x)=4^x-8,\ g(x)=5x+6\\\\\text{Substitute:}\\\\(f+g)(x)=(4^x-8)+(5x+6)=4^x+5x+(-8+6)\\\\(f+g)(x)=4^x+5x-2

User Arbrcr
by
5.4k points